2010
DOI: 10.1177/1947603510383856
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of the Secretome from Dedifferentiated and Redifferentiated Adult Articular Chondrocytes

Abstract: Objective:The main goal of this study was to compare the secretion products derived from human articular chondrocytes established in either long-term monolayer cultures or in scaffold-free 3-dimensional (3-D) cultures.Methods:Stable isotope labeling of amino acids in cell culture (SILAC) was applied to investigate quantitatively the differences between proteins secreted from dedifferentiated and redifferentiated chondrocytes. Proteins in cell supernatants were resolved by 1-D gel electrophoresis and analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The commonly scaffold-free 3D technologies employed for cartilage tissue engineering are based on pellet culture [ 20 ], hanging-drop [ 23 ], and 96-well plate [ 10 , 24 ], with the last two methodologies responsible for spheroid formation. Hanging-drop is a scalable technology; however, spheroids can be maintained in culture only for few days [ 23 ]. Recently, micromolded hydrogels have emerged as an alternative for spheroid culture due to the automation capacity and long-term culture for differentiation assays [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The commonly scaffold-free 3D technologies employed for cartilage tissue engineering are based on pellet culture [ 20 ], hanging-drop [ 23 ], and 96-well plate [ 10 , 24 ], with the last two methodologies responsible for spheroid formation. Hanging-drop is a scalable technology; however, spheroids can be maintained in culture only for few days [ 23 ]. Recently, micromolded hydrogels have emerged as an alternative for spheroid culture due to the automation capacity and long-term culture for differentiation assays [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative assessment of proteins secretome using these proteomic techniques remain hazardous, because the method promotes the The abundance of diverse models used in these proteomics studies also make them difficult to interpret. In monolayer, chondrocytes certainly have a different secretome than in their native 3D environment [31]. In explant culture, the majority of the newly synthesized proteins remains entrapped in the ECM and only degraded products are released into the supernatant [18].…”
Section: Discussionmentioning
confidence: 99%
“…In this part of the review, we focused on proteins identified either directly in the secretome of cartilage explants [12][13][14][15][16][17][18][19][20] or chondrocytes cultures [18,[21][22][23][24][25][26][27][28][29][30][31]), both of which are listed in Table 1. We further complete this list with proteins recently identified by proteomic analysis performed directly on fresh chondrocytes or cartilage tissue [32][33][34][35][36] (sometimes de-cellularized [37]) whereby different locations in the joint were compared, or healthy joint tissues were compared with 6 OA tissues.…”
Section: Chondrocyte Secretomementioning
confidence: 99%
“…In recent years, global proteomic studies based on mass spectrometry approaches have been widely applied to investigate the pathophysiology of articular cartilage (extensively reviewed in [26]). To date, most studies have been focused on proteins directly identified in the secretome of chondrocyte cultures [20,22,24,[27][28][29][30][31][32][33][34][35]. In addition, proteomic analyses were also performed on cartilage tissues and cartilage explants [26].…”
Section: Discussionmentioning
confidence: 99%